Delegation in a multi-tier court system: are remands in the U.S. federal courts driven by moral hazard? - Roee Sarel; Melanie Demirtas (University of Hamburg, Institute of Law and Economics (ILE), 2019)
We analyze the countervailing incentives that mid-level appellate judges face when deciding whether to remand a case back to the lower court. Although appellate courts' ability to remand cases can mitigate moral hazard problems, by restraining trial court judges, it may sometimes instead exacerbate such problems - by enabling the midlevel appellate judges to circumvent the top-level court's preferences through delegation. Our empirical assessment reveals a 'Subsequent Remand Effect': cases that are remanded by the Supreme Court to the appellate court are far more likely to be subsequently remanded again to the district court compared to other cases. We check whether this effect originates from legitimate case-relevant reasons or from moral hazard by exploiting variations in ideological distances between court levels and through a textual analysis. We find that the size of the effect varies with the composition of ideologies, which seems consistent with moral hazard.
Keywords: K41; D02; P48; 330; remands; federal courts; appeals; judicial ideology; ideological distance